Ecological Study on Solid Fuels Use and Pneumonia in Young Children: A Worldwide Association. - Accinelli, Roberto (2019)
In developed countries, tobacco is the main contributor to indoor pollution. However, in developing countries the solid fuels used to cook are the prevailing source of indoor pollution and globally household air pollution is the third highest global risk factor, while it remains the first in South Asia. A recent assessment on the impact of house air pollution in health further reinforces the importance of such factors in global health.